THE EFFECT OF PANCASILA STUDENT PROFILE STRENGTHENING PROJECT (P5) ON STUDENTS' CRITICAL REASONING ABILITY AND LEARNING INDEPENDENCE - Pegy Wulandari; Sri Arita (JURNAL PENDIDIKAN GLASSER, 2025)
he implementation of the Pancasila Student Profile Strengthening Project (P5) is a significant educational reform aimed at developing 21st-century competencies in students. However, empirical evidence regarding its effectiveness on critical thinking skills and independent learning is still limited, especially in the context of vocational education. This study aims to analyze the impact of the P5 implementation on students' critical thinking skills and learning independence at SMK Negeri 2 Pariaman. This study uses a pure experimental method with a pretest-posttest control group design involving 70 students randomly divided into an experimental group (n=35) and a control group (n=35). The experimental group received P5 project-based learning for one semester, while the control group used conventional teaching methods. Data collection utilized validated critical thinking ability tests and learning independence questionnaires, which were then analyzed using descriptive statistics and linear regression analysis. The results of the study indicate a significant negative impact of P5 implementation on students' critical reasoning abilities (B = -1.019, p = 0.021 < 0.05), with both variables achieving moderate levels (TCR = 57%). The discussion indicates that this negative impact is caused by the limited variety of assessment instruments and the mechanical implementation of P5 without pedagogical depth. The study's conclusion emphasizes the need for comprehensive teacher professional development, reflective pedagogical approaches, and enhanced assessment strategies to optimize P5's educational potential